2010
DOI: 10.1016/j.jaci.2009.10.072
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for altered activity of the IL-6 pathway in chronic rhinosinusitis with nasal polyps

Abstract: Background Interleukin 6 (IL-6) activates Th17 cells and regulates the response of B-lymphocytes and T regulatory cells. The IL-6 receptor and the membrane protein, gp130, form an active signaling complex that signals through STAT3 and other signaling molecules. Both the IL-6 receptor (IL-6R) and gp130 can be found in soluble forms that regulate the pathway. Objective We measured IL-6 signaling components and IL-17 in chronic rhinosinusitis with nasal polyps (CRSwNP), CRS without nasal polyps (CRSsNP) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
120
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(135 citation statements)
references
References 66 publications
11
120
1
3
Order By: Relevance
“…[15][16][17][18][19][20] A recent study identified activation of IL-6 (and a possible signaling defect in the IL-6 pathway) in patients with CRS and nasal polyps compared with normal controls. 21 These findings suggest a host characteristic, when coupled with an environmental exposure such as viral URTI that promotes IL-6 production, could potentially explain a …”
Section: Discussionmentioning
confidence: 94%
“…[15][16][17][18][19][20] A recent study identified activation of IL-6 (and a possible signaling defect in the IL-6 pathway) in patients with CRS and nasal polyps compared with normal controls. 21 These findings suggest a host characteristic, when coupled with an environmental exposure such as viral URTI that promotes IL-6 production, could potentially explain a …”
Section: Discussionmentioning
confidence: 94%
“…334,[519][520][521] A precise molecular pathway for this defect has not been proposed, but the cytokine IL-22 and its receptor IL-22R are key regulators of mucosal host defense, 522 acting in large part through the transcription factor STAT 3. 523,524 Diminished expression of IL-22R 525 and blunting of the STAT 3 pathway 526 have been reported; these defects appear to be associated with CRS broadly, and are not specific for the presence or absence of NPs. 527 Taken together, these data provided support for the hypothesis that a primary sinonasal innate immune defect may predispose to the development of CRS.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated IL-6 levels might suggest viral infection 1109 or might be related to the altered IL-6 pathway described in patients with CRS. 526 Bacterial infection also contributes to acute exacerbations and acute purulent episodes in the scenario of underlying chronic inflammatory changes associated with CRS. The frequent presence of biofilm-forming organisms represents a large reservoir for opportunistic infections.…”
Section: Ixb Aecrs: Pathophysiologymentioning
confidence: 99%
“…28 IL-6 plays important roles in regulating Treg and T H 17 differentiation by inhibiting FoxP3, which, in turn, leads to diminished inhibition of the retinoic acid-related orphan receptor ROR␥T and consequently expansion of T H 17 cells. 28 We failed to detect significant amounts of IL-17A, a key cytokine produced by the T H 17 cells in all of our samples, and we did not count T H 17 cells. Nevertheless, the elevation of IL-6 may indicate another mechanism whereby Treg function is inhibited in CRS via a T H 17 mechanism.…”
Section: Discussionmentioning
confidence: 99%